Peran Persepsi Manfaat, Kemudahan, dan Kepercayaan Dalam Mempengaruhi Keinginan Menggunakan QRIS - Wahyuningrum, Maria Y Aryati (INVESTASI : Inovasi Jurnal Ekonomi dan Akuntansi, 2025)
Quick Response Code Indonesian Standard (QRIS) is implemented by Bank Indonesia to make payment transactions simple, efficient, fast, and ethically healthy. Through the use of QR code standards, payment connectivity and interoperability are made possible by QRIS. The population in this study were people who had used QRIS services. The sample taken in this study was 105 respondents. The sampling technique used was primary data where data collection was obtained by distributing online questionnaires to the public. The test tool used was SPSS with several analysis techniques, namely validity test, reliability test, classical assumption test, multiple linear regression, F test, T test, dominant factor, and coefficient of determination (R2). The results of this study indicate that the perception of benefits, convenience, and trust have a partial effect on the interest in use. The perception of benefits, convenience, and trust have a simultaneous effect on the interest in using QRIS, and the most dominant variable on the interest in use is the trust variable.